Universal Access in Human-Computer Interaction. Applications and Services 6th International Conference, UAHCI 2011, Held as Part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011, Proceedings, Part IV - Stephanidis, Constantine.; Stephanidis, Constantine. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2011)
The four-volume set LNCS 6765-6768 constitutes the refereed proceedings of the 6th International Conference on Universal Access in Human-Computer Interaction, UAHCI 2011, held as Part of HCI International 2011, in Orlando, FL, USA, in July 2011, jointly with 10 other conferences addressing the latest research and development efforts and highlighting the human aspects of design and use of computing systems. The 72 revised papers included in the fourth volume were carefully reviewed and selected from numerous submissions. The papers are organized in the following topical sections: speech, communication and dialogue; interacting with documents and images; universal access to education and learning; well being, health and rehabilitation applications; and universal access in complex working environments.